Under locker and key - Hymas, Allison K. (Aladdin Max, 2017)
Jeremy Wilderson is an expert at retrieving other students's stolen property at his middle school. One botched job lands the master key to every locker at school in the hands of a thief, and getting the key back is too much for one person to do alone. So Jeremy will have to work alongside his nemesis, Becca Mills, the one person at school who would love nothing more than to see Jeremy crash and burn.